Roman Law and Qing Dynasty Legal Codes: Zhang Zhidong’s Mediation in the Yichang and Enshi Missionary Incidents - SONG, Huaisi (Journal of Research for Christianity in China (JRCC), 2025)
Beginning in 1891, a series of missionary incidents erupted in the Enshi region of Yichang, Hubei. Zhang Zhidong, the Viceroy of Huguang, formulated management measures to address the religious disturbances, implementing countermeasures that included mediation, arbitration according to law, and the dissemination of official proclamations to dispel rumors, all aimed at stabilizing social order. In the international disputes triggered by missionary incidents during the late Qing period, the Western Roman legal system collided fiercely with the Eastern Chinese legal system embodied in the Qing Dynasty’s legal code. The modern international legal concepts of consular jurisdiction, the right to protect missionaries, and ecclesiastical law broadened the horizons of Qing elites. Following the Boxer Rebellion, Empress Dowager Cixi and Emperor Guangxu fled westward. The Qing central government recognized the severe crisis threatening the dynasty. Proposals by figures like Huguang Governor-General Zhang Zhidong to learn from the West and reform the legal system were implemented during the late Qing New Policies, propelling the modernization of China’s rule of law.